2004
DOI: 10.1038/sj.ejcn.1601923
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrient intake in East and West Germany, 8 years after the reunification—The German Nutrition Survey 1998

Abstract: Objective: To explore differences in food and nutrient intake as well as cardiovascular risk factors between the eastern and western parts of Germany in 1998 and to compare food consumption information between 1991 and 1998. Design and subjects: In all, 4030 people, aged 18-79 y, sampled from the East and West parts of Germany participated in the German Nutrition Survey (1998) by completing dietary histories and being assessed for cardiovascular risk factors. In a separate analysis, two food frequency data set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 7 publications
4
47
0
1
Order By: Relevance
“…National dietary surveys from Austria (Elmadfa et al, 2009a), France (Afssa, 2009), Germany (Mensink and Beitz, 2004), Hungary (Bíró et al, 2007), Ireland (IUNA, 2011) and the UK (Henderson et al, 2003) reported mean daily intake estimates for manganese ranging from 2.5 to 6.6 mg in men and from 2.0 to 5.5 mg in women, with most values around 3 mg/day.…”
Section: Adultsmentioning
confidence: 99%
“…National dietary surveys from Austria (Elmadfa et al, 2009a), France (Afssa, 2009), Germany (Mensink and Beitz, 2004), Hungary (Bíró et al, 2007), Ireland (IUNA, 2011) and the UK (Henderson et al, 2003) reported mean daily intake estimates for manganese ranging from 2.5 to 6.6 mg in men and from 2.0 to 5.5 mg in women, with most values around 3 mg/day.…”
Section: Adultsmentioning
confidence: 99%
“…The response rate was 61.4% (Bellach et al, 1998;Thefeld et al, 1999). The sampling procedure has been previously described in detail (Mensink and Beitz, 2004). The present analysis is based on a random subsample of 2267 women and 1763 men who also participated in an extended dietary assessment, the German Nutrition Survey 1998.…”
Section: Subjectsmentioning
confidence: 99%
“…As an exception, we attempted to cover the largest possible proportion of women of childbearing age assuring a sufficient number of participants for the allied folic acid study. To correct for this disproportionality as well as for discrepancies due to nonresponse and noncoverage between the net sample and the situation of the German population according to age, gender, community size and residence in West or East Germany in 1998, a weighting factor was computed (Mensink and Beitz, 2004). Surveys were approved by the federal data protection office.…”
Section: Subjectsmentioning
confidence: 99%
“…It is reported that calcium content in drinking water is positively related to systolic blood pressure and has also served as a risk factor for cardiovascular diseases. 7 In 1999, Yang and Chiu documented that there is a significant protective effect of magnesium intake from drinking water on the risk of hypertension, 8 which leads to the speculation that magnesium plays an important role in blood pressure regulation. The potential mechanisms for magnesium to lower blood pressure might be (a) the dilatation of renal vessels; (b) the acceleration of prostaglandin release; (c) the stimulation of sodium pumping and adenosine kinase, which is increased in case of magnesium loss; (d) the regulation by renin of magnesium can make the blood vessels constricted.…”
Section: Discussionmentioning
confidence: 99%